F(x)=
to solve for the inverse of a function you do 4 steps:
1. subsitute f(x) with y
2. switch y and x places
3. solve for y
4. subsitute y with f⁻¹(x)
so we have
f(x)=
subsitute f(x) with y
y=
switch x and y
x=
solve for y
x=
cube both sides
=y+2
subtract 2 from both sides
=y
subsitute y with f⁻¹(x)
f⁻¹(x)=
the answer is f⁻¹(x)=
Answer:
6 pairs of socks
Step-by-step explanation:
I started with $15.99 and subtracted that by $21.93. $21.93-$15.99= $5.94. Then I divided $5.94 by $0.99. $5.94/$0.99= 6. I hope this helped
Answer:
6. 5 % is the answer
Step-by-step explanation:
formula =
<em>R</em><em> </em><em>=</em><em> </em><em>I</em><em> </em><em>×</em><em> </em><em>1</em><em>0</em><em>0</em><em> </em><em>/</em><em> </em><em>P</em><em> </em><em>×</em><em> </em><em>T</em>
Answer: C) F(4) = 0
Detailed Explanation:
A zero/root of a polynomial is a value of the variable which makes the value of the polynomial to 0.
Therefore, when (x - 4) is a Factor :-
=> x - 4 = 0
=> x = 4
=> x = 4 is the Zero of the Polynomial.